Estimation of Transition Probabilities for the Illness-Death Model: Package TP.idm - Balboa, Vanesa; de Uña-Álvarez, Jacobo (Journal of Statistical Software, 2018)
In this paper the R package TP.idm to compute an empirical transition probability matrix for the illness-death model is introduced. This package implements a novel nonparametric estimator which is particularly well suited for non-Markov processes observed under right censoring. Variance estimates and confidence limits are also implemented in the package.